The Practice Of Strategic Management Accounting In Public Sector Indonesia - Sriyono; Effendi, Mohamad Irhas; Sirait, Afni (Jurnal Akuntansi, 2024)
Market orientation, cost leadership strategies, strategic management accounting practices, competitor accounting, and customer accounting of village-owned enterprises in Indonesia were the focus of this study's effort to identify empirical evidence of a causal link between them. Village-owned businesses in Indonesia and the role manager of those businesses are the subjects of this quantitative study. Applying SMA practice-competitor Accounting and SMA practice-customer Accounting in supported Village Owned Enterprises in Indonesia is positively impacted by market orientation and cost leadership strategies. This paper offers empirical proof that SMA Practice-Customer Accounting and SMA Practice-Competitor Accounting have been created and implemented in Indonesian village-owned businesses, with implications for theory. These findings corroborate the contingent hypothesis, which holds no universally applicable rules.